Introducing human geography : (Longman, 2000)
A comprehensive new introduction to Australian and Aotearoa/New Zealand human and cultural geography. The authors integrate key themes of globalisation, difference and inequality into this student friendly book. Each chapter follows a strong pedagogical framework designed to enhance students' ability to understand the material.